Approaching atrial septal defects in pulmonary hypertension. (June 2015) - Schwerzmann, Markus; Pfammatter, Jean-Pierre
<x xml:space="preserve">Abstract</x> Atrial septal defects (ASDs) are one of the most frequent congenital cardiac malformations, accounting for about 8–10% of all congenital heart defects. The prevalence of pulmonary arterial hypertension (PAH) in adults with an ASD is 8–10%. Different clinical PAH scenarios can be encountered. At one end of the spectrum are adults with no or only mild pulmonary vascular disease and a large shunt. These are patients who can safely undergo shunt closure. In the elderly, mild residual pulmonary hypertension after shunt closure is the rule. At the other end of the spectrum are adults with severe, irreversible pulmonary vascular disease, shunt reversal and chronic cyanosis, that is, Eisenmenger syndrome. These are patients who need to be managed medically. The challenge is to properly classify ASD patients with PAH falling in between the two ends of the spectrum as the ones with advanced, but reversible pulmonary vascular disease amenable to repair, versus the ones with progressive pulmonary vascular disease not responding to shunt closure. There are concerns that adults with progressive pulmonary vascular disease have worse outcomes after shunt closure than patients not undergoing shunt closure. Due to the correlation of pulmonary vascular changes and pulmonary hemodynamics, cardiac catheterization is used in the decision-making process. It is important to consider the hemodynamic data in the context of the clinical picture, the defect anatomy and further noninvasive tests when evaluating the option of shunt closure in these patients.